Cyber Crimes Against the Impact of Communication Behavior Social Media in Facebook Adolescent Jakarta - Herlina, Mira (International Journal of Psychosocial Rehabilitation, 2020)
Indonesia is a country that can not be separated from cybercrime because the current growth of the Internet and its use is rapidly in Indonesia. Socially mediated crime will lead to changes in the behavior of adolescent communication, especially between the age of 16 to 25 years. Based on data from 2018 APJII almost 49.52% of active Internet users today are teens at age 16 to 35 years. The behavior of adolescent communication in social media has been very concerned about this can be seen from the behavior of adolescent communication in interaction via social media facebook. This is due to the deterioration of manners act irresponsible, damaging and worrying and actions that harm others. This study therefore very necessary to determine how big the impact of cybercrime on the behavior of communication in social media facebook in adolescents in Jakarta. This study using the quantitative methodology by spreading the questionnaire to 100 teenagers in Jakarta. The results showed a significant effect on the behavior of cybercrime communication in social media facebook in adolescents in Jakarta. Research related to cybercrime has been carried. So the conclusion is that there is a cybercrime affected the behavior of adolescents Jakarta communication in social media facebook because of the many social media facebook user who spread out the information lies, use photos of other people in your account,